Effects of an Online Solution-Focused Psychoeducation Programme on Children’s Emotional Resilience and Problem-Solving Skills - Özdemir, Melih Burak; Bengisoy, Ayşe (Frontiers in Psychology, 2022)
The present study investigates the effects of a solution-oriented and approach-based psychoeducation programme, initiated in December 2019 and conducted online during the worldwide Covid-19 pandemic, on children’s emotional resilience and problem-solving skills. In the world that was closed with the pandemic, children were kept away from the social support system of teachers and friends. Pandemic isolated the children. The negative experiences associated with Covid-19 have placed both traditional approaches and important online learning and support applications on the agenda, since both can help to solve the problems we face. Educators and experts have provided psychological support services, questioning the methods used to reach people during the pandemic and rediscovering alternative ways of connecting with individuals through online media. The online framework of this study emerged in response to the needs caused by the pandemic. The study is designed using real experimental pattern and based on a pretest-posttest, experimental/control-group model. The Social Support Evaluation Scale for Children and Teenagers was used to select the participants. 18 participants were equally assigned to research groups (experiment n=9, control n=9). The psychoeducation programme consisted of six sessions, each lasting 50–60 minutes on average. Research carried out online during the pandemic shows that this psychoeducational programme is effective in strengthening students’ problem-solving and emotional-resilience skills. These findings are discussed within the framework of the literature, followed by recommendations.